Edukasi Keluarga dalam Mengatasi Stres Perawatan Orang Skizofrenia di Desa Penyengat Olak Jambi Luar Kota Muaro Jambi - Daryanto Daryanto; Mursidah Dewi; Yellyanda Yellyanda (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Caring for people with schizophrenia is one of the stressfull. Families do not get information on how to cope the stress experienced. This can affect the recurrence of schizophrenic patients. Families have never received education how to deal with stress. The purpose of community service activities is to increase family knowledge in dealing with stress in the care of people with schizophrenia. The method is carried out through classical learning such as lectures, discussions, and simulations and followed by mentoring through whatsup groups and direct supervision. This service activity has been carried out from the period August to September 2022 in Penyengat Olak Village. A total of 40 participants consisting of 26 family caregivers of people with Skizofrenia, 9 mental health cadres, 5 people from the leadership and staff of the puskesmas and the village have participated in the entire series of activities. The results showed an increase in capabilty to cope stress in caring for people with schizophrenia (Pv 0.000). Handbooks are useful for families in dealing with the daily stress of caring. Family caregivers have used stress coping techniques and created activity schedules as a way of applying stress coping techniques. Family caregivers are expected to implement the stress coping technics using the guidelines provided. The Community mental health Nurse and village health cadres are expected to monitor and report on families stress and provide consulting services on how to deal with stress and make referrals to families experiencing severe stress.